"To Study the Potential Of Spear Grass As An Additional Material In Brick " - MOHAMMAD KHAIRUL AMIR BIN MOHD RAZUAN (Progress in Engineering Application and Technology, 2023)
Imperata cylindrica or well known as spear grass is the most difficult and competitive weeds to control in agriculture. The use of spear grass in the making of brick will give an economical value to it as well as to reduce the amount of clay use. Spear grass brick was made to ensure the strength and water absorption when adding spear grass in the brick. It also to discover and produce a new product in construction industry. The ratio for the design mix of brick produced was 1:5:12. Spear grass with mix 0%, 1% and 2% were incorporate into the brick. The spear grass will cut into 10mm ± 20mm lengths then sieve to ensure all size were equivalent. Thirty six (36) numbers of brick will be produced with dimension 215 x 102.5 x 65 mm (length x width x height) for seven (7) and fourteen (14) days curing. The testing of compressive strength, water absorption, and dimension will be done to obtain a result. In comparison to 2% of spear grass, which achieved 4.06 MPa in 14 days, 1% of spear grass had the maximum compressive strength at 4.70 MPa. When, the spear grass add in the brick mix, the compressive strength of the brick decreases. According to test results, spear grass mix is more water-absorbent than regular brick. For both the 7 and 14 days periods, 1% is the maximum percentage of water absorption. There no major different between the standard requirement and spear grass brick size but still can acceptable in dimension test.